Dampak Pandemi Covid-19 Terhadap Tingkat Occupancy - Ramantha, Ngakan Putu Gede; Suwintari, I Gusti Ayu Eka; Suarmana, I Wayan Restu (Institut Pariwisata dan Bisnis Internasional, 2024)
Pemanfaatan kapasitas adalah rasio jumlah kamar yang disewa atau disewa oleh pelanggan dengan jumlah kamar yang disewa. Penelitian ini bertujuan untuk mengetahui dampak pandemi Covid19 terhadap hunian Villa JJ dan SPA Ubud, Bali serta untuk mengetahui upaya apa saja yang dilakukan Villa JJ dan SPA Ubud, Bali dalam menangani kasus Covid19. Penelitian ini menggunakan data kualitatif berupa wawancara, observasi dan dokumen tentang hunian di Villa JJ dan SPA Ubud, Bali. Berdasarkan hasil penelitian, dampak pandemi Covid-19 terhadap tingkat hunian di Villa JJ dan SPA Ubud, Bali, dibandingkan tahun 2020 antara Januari dan Desember, tingkat hunian yang ia isi di Villa JJ dan SPA Ubud, Bali adalah cukup bagus, mulai 10 kamar, rata-rata terisi 7 kamar per hari, jadi kapasitas sewa berkisar 55% atau lebih. Namun, pada tahun 2021, Januari-Desember akibat pandemi Covid-19, penjualan kamar turun signifikan hingga 5% dari total kamar. kemudian pada tahun 2022 meningkat menjadi 40%. Dan mengenai upaya peningkatan okupansi Villa JJ And Spa Ubud, Bali salah satunya adalah menarik wisatawan untuk berwisata di Bali khususnya Villa JJ And Spa Ubud, Bali. Berbagai cara telah dilakukan untuk menarik wisatawan, misalnya dengan memberikan diskon atau pengurangan tarif kamar. Occupancy is the proportion of rooms which are occupied or rented out to visitors in comparison to the entire variety of rooms which are rented out. This have a look at pursuits to decide the effect of the Covid-19 pandemic on Occupancy fees at Villa JJ and Spa Ubud, Bali and to discover what efforts may be made. This turned into executed through Villa JJ and Spa Ubud, Bali in tackling the Covid-19 case. This have a look at makes use of qualitative records withinside the shape of interviews, observations and documentation approximately the occupancy fee at Villa JJ and Spa Ubud, Bali. Based at the effects of the have a look at, the effect of the Covid-19 pandemic on the extent of Occupancy at Villa JJ and Spa Ubud, Bali, that during 2020 withinside the length from January to December the Occupancy fee at Villa JJ and Spa Ubud, Bali turned into pretty good, out of 10 current rooms. a median of seven rooms occupied consistent with day, so the Occupancy fee levels from 55% and above. However, in 2021 from January-December because of the Covid-19 pandemic, room income reduced substantially to attain 5% of the entire rooms. Then in 2022 it's going to boom once more to 40%. And as for the efforts made to boom Occupancy at Villa JJ and Spa Ubud, Bali, one in every of them is through attracting travelers to excursion in Bali, specifically to Villa JJ and Spa Ubud, Bali. Various methods were carried out to draw travelers, which includes presenting reductions or room fee reductions.